Spatial conflicts in residential neighbourhoods with blocks of flats in Maribor (Slovenia) - Drozg, Vladimir (Journal for Geography, 2018)
The paper deals with spatial conflicts in blocks residential neighbourhoods in Maribor, Slovenia. Numerous neighbourhood arrangements from 50 years ago today don’t correspond to the current conditions and needs. In areas, where there was no real adaptation to new living needs and new circumstances, a lot of discrepancies have emerged between what is and what should be there. Several spatial conflicts have been recognised: conflicts in land use, mostly due to decrease of open green areas, visual degradation of residential buildings (poorly maintained open places, air conditioners on facade facilities and garbage containers in public places create a bad appearance of the neighbourhood), conflicts in dynamic and dormant traffic due to lack of parking places, conflicts in accessibility to basic supply and service activities and the abandonment of social spaces.